Detection of Food Poisoning (Bacillus cereus) Pathogen in Cooked and Refrigerated Rice Samples: Food Poisoning Pathogen in Refrigerated Rice - Shaikh, Shagufta Ambreen; Sidiqui, Anila; Naz, Shagufta; Ismat, Seema (Biological Sciences - PJSIR, 2019)
Rice is a staple food of Pakistan. It is being contaminated with several food poisoning causing bacterial and mold contaminants. In this study 100 different rice samples were collected from local market of Karachi city. The presence of Bacillus cereus vegetative cell and survival of their spores were quantitavely analyzed after cooking and refrigeration. From the study it was observed that out of 100 rice samples, 25% cooked/refrigerated samples were positive for the presence of B.cereus spores , even there were few samples which showed increase of count due to improper (cooking and refrigeration ) which causes the germination and proliferation of spores into vegetative cells under favorable conditions. The detection of increased count of B. cereus even after cooking and refrigeration treatments is very alarming since cooking is supposed to be best treatment given to the raw food. Different rice dishes are being frequently consumed by the general population and are also available on different shops (as biryanis or fried rice), hence, detection of B. cereus in cooked rice samples will be useful to control any outbreak of food poisoning cases especially in summer seasons.